2017
DOI: 10.2754/avb201786020175
|View full text |Cite
|
Sign up to set email alerts
|

The determination of minimum inhibitory concentrations of selected antimicrobials for porcine Haemophilus parasuis isolates from the Czech Republic

Abstract: Haemophilus parasuis isolates obtained from pigs in the Czech Republic were tested for their susceptibility to amoxicillin, penicillin, ceftiofur, enrofloxacin, tetracycline, and tulathromycin by determination of minimum inhibitory concentrations using the broth microdilution method. The H. parasuis isolates were mostly susceptible to majority of tested antimicrobials (amoxicillin 90%, penicillin 73.3%, enrofloxacin 83.3%, and tulathromycin 83.3%). All isolates were susceptible to ceftiofur. On the other hand,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…Serotypes 5 and 4 are dominant in China [3]. With the abuse of antibiotics, antimicrobial-resistant G. parasuis emerge in different degrees, which bring serious threat to the global economy and public health [4].…”
Section: Introductionmentioning
confidence: 99%
“…Serotypes 5 and 4 are dominant in China [3]. With the abuse of antibiotics, antimicrobial-resistant G. parasuis emerge in different degrees, which bring serious threat to the global economy and public health [4].…”
Section: Introductionmentioning
confidence: 99%
“…For macrolides, two studies from Europe reported data for tulathromycin . One of them, with data from Denmark, France and Germany, found full susceptibility among 68 isolates (El Garch et al., 2016 ), and the other with data from the Czechia reported 13.3% of 30 isolates resistant (Nedbalcová et al., 2017 ). Three studies reported data for erythromycin with resistance proportions ranging from 1.8% to 50%.…”
Section: Assessmentmentioning
confidence: 99%
“…There are no internationally recognised CBP for G. parasuis , but at least three of the studies from which data were extracted (Zhou et al., 2010 ; El Garch et al., 2016 ; Nedbalcová et al., 2017 ) had adapted the CLSI breakpoints available for A. pleuropneumoniae and/or P. multocida . Some other studies also referred to CLSI breakpoints, but for those it was unclear if they had used the same approach (e.g.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of in vitro susceptibility testing of A. pleuropneumoniae, P. multocida and H. parasuis to antimicrobials, the aminopenicillins (amoxicillin), and fluoroquinolones appear to be suitable for the treatment of infections caused by these pathogens in the field due to the high efficiency and relatively low level of resistance. However, some of the commonly used antimicrobials for treatment of respiratory infections of pigs are becoming less effective due to increased resistance among bacterial pathogens in recent years (Aarestrup et al 2004;Cai et al 2005;De la Fuente et al 2007;Nedbalcova and Kucerova 2013;de Jong et al 2014;Nedbalcova et al 2014;El Garch et al 2016;El Garch et al 2017;Nedbalcova et al 2017;Sweeney et al 2017). The number of effective treatment options is limited, partially due to the recent regulations, such as in the case of third-and fourth-generation cephalosporines, which are coming under more scrutiny due to the associated evolution of extended-spectrum betalactamase resistance genes.…”
mentioning
confidence: 99%